2020
DOI: 10.1167/jov.20.4.2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the temporal and spatial properties of trans-saccadic perceptual recalibration and saccadic adaptation

Abstract: Repeated exposure to a consistent trans-saccadic step in the position of the saccadic target reliably produces a change of saccadic gain, a well-established trans-saccadic motor learning phenomenon known as saccadic adaptation. Trans-saccadic changes can also produce perceptual effects. Specifically, a systematic increase or decrease in the size of the object that is being foveated changes the perceptually equivalent size between fovea and periphery. Previous studies have shown that this recalibration of perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 53 publications
5
35
0
Order By: Relevance
“…The observed modification of size perception was in line with several studies that demonstrated an interaction between the motor adaptation with a distortion of visual localization of the target executed by hand pointing or by perceptual reports (Awater, Burr, Lappe, Morrone, & Goldberg, 2005;Bahcall & Kowler, 1999;Bruno & Morrone, 2007;Collins, Doré-Mazars, & Lappe, 2007;Garaas & Pomplun, 2011;Gremmler, Bosco, Fattori, & Lappe, 2014;Zimmermann & Lappe, 2010). Several more recent studies have indicated that adaptation of visual features can be found without saccadic adaptation (Herwig & Schneider, 2014;Herwig, Weiß, & Schneider, 2015;Herwig, Weiß, & Schneider, 2018;Köller, Poth, & Herwig, 2020;Paeye, Collins, Cavanagh, & Herwig, 2018;Valsecchi & Gegenfurtner, 2016;Valsecchi, Cassanello, Herwig, Rolfs, & Gegenfurtner, 2020). Specifically, features for which this phenomenon occurs are spatial frequency (Herwig & Schneider, 2014;Herwig et al, 2018), shape (Herwig et al, 2015;Köller et al, 2020;Paeye et al, 2018) and size (Bosco et al, 2015;Valsecchi & Gegenfurtner, 2016;Valsecchi et al, 2020).…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…The observed modification of size perception was in line with several studies that demonstrated an interaction between the motor adaptation with a distortion of visual localization of the target executed by hand pointing or by perceptual reports (Awater, Burr, Lappe, Morrone, & Goldberg, 2005;Bahcall & Kowler, 1999;Bruno & Morrone, 2007;Collins, Doré-Mazars, & Lappe, 2007;Garaas & Pomplun, 2011;Gremmler, Bosco, Fattori, & Lappe, 2014;Zimmermann & Lappe, 2010). Several more recent studies have indicated that adaptation of visual features can be found without saccadic adaptation (Herwig & Schneider, 2014;Herwig, Weiß, & Schneider, 2015;Herwig, Weiß, & Schneider, 2018;Köller, Poth, & Herwig, 2020;Paeye, Collins, Cavanagh, & Herwig, 2018;Valsecchi & Gegenfurtner, 2016;Valsecchi, Cassanello, Herwig, Rolfs, & Gegenfurtner, 2020). Specifically, features for which this phenomenon occurs are spatial frequency (Herwig & Schneider, 2014;Herwig et al, 2018), shape (Herwig et al, 2015;Köller et al, 2020;Paeye et al, 2018) and size (Bosco et al, 2015;Valsecchi & Gegenfurtner, 2016;Valsecchi et al, 2020).…”
Section: Introductionsupporting
confidence: 89%
“…Many studies demonstrated that saccadic adaptation includes a mechanism that calibrates visual space perception by observing and correcting mismatches between the peripheral view of a target and the central view of the same target after a saccade toward it (Awater et al, 2005;Bahcall & Kowler, 1999;Bruno & Morrone, 2007;Collins et al, 2007;Garaas & Pomplun, 2011;Gremmler et al, 2014;Zimmermann & Lappe, 2010;Zimmermann & Lappe, 2016). As mentioned earlier, similar to changing position of the target in the traditional saccadic adaptation paradigm, other features such as spatial frequency (Herwig & Schneider, 2014), shape (Herwig et al, 2015;Köller et al, 2020;Paeye et al, 2018), and size (Bosco et al, 2015;Valsecchi & Gegenfurtner, 2016;Valsecchi et al, 2020) also appear adaptive across saccades. However, similar effects on shape and size perception have also been observed when objects were successively presented in peripheral and foveal view while observers maintained fixation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Such a prior should predict a specific perceived size according to eccentricity, and any deviation from this prediction would trigger the updating of the peripheral size percept. This updating should be fast 27 to maintain stability across the visual field and ensure efficient interactions with the environment. When perception stabilized, any perceived difference could then signify a veridical change in the size of the object or of its viewing distance.…”
Section: Discussionmentioning
confidence: 99%